2012
DOI: 10.1002/pip.2297
|View full text |Cite
|
Sign up to set email alerts
|

From high‐efficiency n‐type solar cells to modules exceeding 20% efficiency with aluminum‐based cell interconnection

Abstract: We present the integrated development of back-contacted solar cells and an adequate module interconnection for a highefficiency photovoltaic module. We report on a large area (125 Â 125) mm 2 back-junction back-contact n-type solar cell metallized with aluminum having a total area conversion efficiency of 20.7%. To transfer the high conversion efficiency to the module, we use the laser welding process named aluminum-based mechanical and electrical laser interconnection for module integration of these back-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In general, the metallization geometry of the solar cell features an interdigitated finger structure and busbars collecting the current from the individual fingers. Simulations and measurements have shown that the busbar regions of the BJBC solar cells reduce the fill factor and short-circuit current density [5][6][7]. Other extended structures like contact areas with several tens of square millimeters cause similar problems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, the metallization geometry of the solar cell features an interdigitated finger structure and busbars collecting the current from the individual fingers. Simulations and measurements have shown that the busbar regions of the BJBC solar cells reduce the fill factor and short-circuit current density [5][6][7]. Other extended structures like contact areas with several tens of square millimeters cause similar problems.…”
Section: Introductionmentioning
confidence: 99%
“…In this work we are presenting the module integration of busbar‐free BJBC solar cells by means of a simplified multilevel metallization. We contact each individual base and emitter finger to an Al foil using the aluminum‐based mechanical and electrical laser interconnection (AMELI) process . A polymer layer insulates the base from the emitter metallization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation